FOR US, WOMEN ARE SACRED: GENDER AND CONFLICT IN THE CASAMANCE - Rudolf,Markus (2021)
Abstract The paper examines the changes of gender relations and power inequalities in a context of nearly forty years intermittent war. It shows that gender roles have been both changing and consolidating during the conflict. Furthermore, analysis reveals a multipolar instead of a bipolar local conceptualisation of gender. Social youth differs from breadwinners on the male and mothers on the female side. The conflict has catalysed the development of new social positions for women (cheffe de ménage), new pathways to achieve social adulthood for men (combattant), reinforced customary gender relations (workload, role in the community), but it also thwarted gendered synergies in the traditional division of labour (breadwinner, childcare); being one of the contested ideological values, the conflict has finally - with certain exceptions - rather reinforced than weakened the protection of women against SGBV.